2019
DOI: 10.1161/circheartfailure.118.005897
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Bioprofiles and Mechanistic Pathways of Progression to Heart Failure

Abstract: Background: Identifying the mechanistic pathways potentially associated with incident HF may provide a basis for novel preventive strategies. Methods and Results:To identify proteomic biomarkers and the potential underlying mechanistic pathways that may be associated with incident HF defined as first hospitalization for HF, a nestedmatched case-control design was used with cases (incident HF) and controls (without HF) selected from 3 cohorts (>20,000 individuals). Controls were matched on cohort, follow-up tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 65 publications
4
64
0
1
Order By: Relevance
“…Apart from that, cell apoptosis induced by inflammatory cytokines also participates in the occurrence and development of chronic HF [34]. Related studies have found clusters of biomarkers related to the mechanism of HF in the aspects of inflammation, apoptosis, vascular function, and so on [35]. Our results showed that YXS decreased the TUNEL-positive rate and caspase-3 activity while it increased the mitochondrial membrane potential, which demonstrated an obvious inhibition of cell apoptosis by YXS.…”
supporting
confidence: 56%
“…Apart from that, cell apoptosis induced by inflammatory cytokines also participates in the occurrence and development of chronic HF [34]. Related studies have found clusters of biomarkers related to the mechanism of HF in the aspects of inflammation, apoptosis, vascular function, and so on [35]. Our results showed that YXS decreased the TUNEL-positive rate and caspase-3 activity while it increased the mitochondrial membrane potential, which demonstrated an obvious inhibition of cell apoptosis by YXS.…”
supporting
confidence: 56%
“…S2). [34][35][36][37][38] Such observations further support the concept of incident heart failure triggered by acute kidney injury.…”
Section: Pathoph Ysiol Ogymentioning
confidence: 58%
“…[35][36][37] Recently, in a nested, matched, case-control study involving patients with incident heart failure, 89 of 252 circulating plasma proteins in the discovery set and 38 in the replication set were associated with heart failure. 38 Furthermore, for these validated proteins, four major pathways were involved: inflammation and apoptosis; growth, angiogenesis, and extracellular-matrix remodeling; metabolism; and the renin-angiotensin-aldosterone system. [34][35][36][37][38] Two of the identified proteins, insulin-like growth factor-binding protein 7 (IGF-BP7), a biomarker of cell-cycle arrest, and kidney injury molecule 1 (KIM-1), are also increased during kidney injury.…”
Section: Pathoph Ysiol Ogymentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that IGFBP2 surprisingly and notably adds to the diagnostic and prognostic value of BNP suggests that IGFBP2 features a different pathophysiological background than natriuretic peptides. Yet, achieving a comprehensive view on the current evidence regarding IGFBP2 and its link with natriuretic peptides and HF remains challenging: complex network analysis is an increasingly used 3 analysis strategy allowing such integrated view of available evidence.…”
Section: Bnpmentioning
confidence: 99%